Improved patient outcomes using the enhanced recovery pathway in breast microsurgical reconstruction: a UK experience. (March 2019) - Sindali, K.; Harries, V.; Borges, A.; Simione, S.; Patel, S.; Vorster, T.; Lawrence, C.; Jones, M.
Summary: Introduction: The enhanced recovery after surgery (ERAS) pathway is a protocol aimed at optimizing patient care by reducing the physiological alterations caused by surgery, thus reducing recovery time, surgical morbidities and length of stay. This study assessed the impact of ERAS on patients undergoing microsurgical breast reconstruction. Methods: Patients undergoing microsurgical breast reconstruction over an eight-month period were retrospectively examined. LOS, complication rates and perioperative outcomes were analysed. Results were compared between patients admitted on the traditional recovery after surgery (TRAS) and the ERAS pathways. Results: One hundred and thirty-eight patients were included. Seventy-two patients were admitted on the TRAS pathway and 66 patients on the ERAS pathway. There was no difference in median LOS (4 days) between the two groups, p = 0.48. We noted a significant reduction in the total number of major complications (ERAS 11%, TRAS 24% p = 0.04) as well as significant differences in time to catheter removal, time to independent mobilisation, total opioid usage and time to removal of PCA, all in favour of the ERAS group. There was a non-significant reduction in return to theatre and readmission rate in the ERAS group (11% versus 21% p = 0.1 and 6% versus 11% p = 0.29 respectively). Obesity and complications were predictors of a prolonged LOS. Conclusion: The ERAS pathway reduced overall and major complication rates in a tertiary centre using an already streamlined service. Adoption of ERAS pathways to reduce surgical morbidities and improve patient care is encouraged. Further work is required to optimise enhanced recovery in breast microsurgical reconstruction.